2017
DOI: 10.1111/cmi.12785
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro model for haematogenous spreading ofS. aureusdevice biofilms demonstrating clumping dispersal as an advantageous dissemination mechanism

Abstract: Staphylococcus aureus is able to disseminate from vascular device biofilms to the blood and organs, resulting in life-threatening infections such as endocarditis. The mechanisms behind spreading are largely unknown, especially how the bacterium escapes immune effectors and antibiotics in the process. Using an in vitro catheter infection model, we studied S. aureus biofilm growth, late-stage dispersal, and reattachment to downstream endothelial cell layers. The ability of the released biofilm material to resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…These results support previous studies, showing a high prevalence of genes of the icaA and icaD loci among S. aureus mastitis isolates 32 , 33 . As reported for the clumping dispersal in S. aureus bloodstream infections 34 , high levels of PNAG in biofilm could be an advantageous dissemination mechanism by facilitating staphylococcal bacteria-to-bacteria interaction, which mediates the dispersal ability of the pathogen in the bovine mammary gland.…”
Section: Discussionmentioning
confidence: 66%
“…These results support previous studies, showing a high prevalence of genes of the icaA and icaD loci among S. aureus mastitis isolates 32 , 33 . As reported for the clumping dispersal in S. aureus bloodstream infections 34 , high levels of PNAG in biofilm could be an advantageous dissemination mechanism by facilitating staphylococcal bacteria-to-bacteria interaction, which mediates the dispersal ability of the pathogen in the bovine mammary gland.…”
Section: Discussionmentioning
confidence: 66%
“…Before the discovery of PIA, some studies reported an impact of slime production on the pathogenesis of S. epidermidis device-related infection [147] and an association with origin from infection, for example from nosocomial bacteremia [148] , while others did not [148] , [149] . In addition to the assumption that clumping/slime production increases the success of infections on indwelling medical devices, recent research also has suggested that this phenotype increases the chances of staphylococcal dissemination through the bloodstream [150] .…”
Section: Pia In Infectionmentioning
confidence: 99%
“…Of note, we have obtained preliminary results showing that the method can be conducted with live endothelial cells using diluted human plasma as only source of nutrients. This provides an even more physiological correct medium that both supports S. aureus growth and endothelial viability and further contains fibrinogen and coagulation components which are used by S. aureus to form thrombotic biofilms (Grønnemose et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this requires termination of a rather laborious experiment, leaving only a single data point measured per chamber. Furthermore, CFU enumeration of bacteria exposed to in vivo -like stress conditions can be tricky, since bacteria may change morphology, i.e., become filamentous (Klein et al, 2015 ; Khandige et al, 2016 ), or aggregate (Loof et al, 2015 ; Grønnemose et al, 2017 ; Sønderholm et al, 2017 ), or slow down growth speed (Proctor et al, 2006 ), which may affect the accuracy of bacterial quantification by traditional plating techniques.…”
Section: Introductionmentioning
confidence: 99%